Citizen engagement and collaboration: The key to promoting learning city - Kathanyoo Kaewhanam; Phimlikid Kaewhanam; Ariya Pongsiri; Jariya Intanin; Sirinada Kamolkat; Noppakun Thongmual (Journal of Education and Learning (EduLearn), 2023)
The urban development of learning is a key goal of the United Nations Educational, Scientific, and Cultural Organization (UNESCO). However, the drive to achieve urban learning requires several key points. Citizenship and cooperation are associated with developing the city of learning. This research studies the relationship between citizenship and cooperation in driving the learning city. The study uses the methodology of the structure-equation model (SEM) to study citizenship relationships. Cooperation and learning cities are based on civic data analysis of 500 samples. The result showed that the two observed variables were public participation and The four observed variables are: policy collaboration's positive effect on cooperation; citizen-subjectivity, citizen-intersubjectivity, citizen-sub politics, and citizen-globality's positive effect on citizenship; Furthermore, the six observed variables are: inclusive learning in the education system; revitalized learning in families and communities; effective learning for and in the workplace; expanded use of modern learning technologies; improved learning quality; and a vibrant culture of lifelong learning. In part of the regression between latent variables, we found that cooperation has a positive effect on learning cities (b=0.882), and citizenship has a positive effect on learning cities (b=0.056) and cooperation (b=0.217).